Incentives for Healthy Behavior - Rhodes, Rosamond (The Hastings Center report, 2015)
In recent years, pay-for-performance initiatives have been employed to encourage desired behavior in various domains, including health. Employers use money to encourage employees to exercise; and hospitals, to encourage physicians to practice efficiently. Now, medical groups are considering the use of payments to encourage people to accept often-avoided medical interventions, such as mammography or stool sampling. For example, a panel at the New York United Hospital Fund and the Greater New York Hospital Association Foundation's 2014 Annual Symposium on Health Care Services discussed how patient incentives could prevent illness, mitigate the impact of disease, save lives, and conserve medical resources and money.